FAITH BELIEF TRADITION - Podgorski, Frank R (Journal of Dharma, 1981)
A senseless barbaric arms-race! Staggering abuses of the most basic of human rights! An impending nuclear holocaust! Global economic fright! Poverty and suffering to an extent never before experienced in human history! Yet. somehow and in some way. religions and religious convictions perdure. In spite of. or perhaps because of such harsh realities. religions and religious perspectives and religious values remain a foundational element of contemporary experience. Islam, Christianity, Hinduism. Buddhism. Marxism. Tribal Religions still form. inform. and create human values and perspectives. How is this still possible? Why? Is Our Age still able to "stand-under" the spell of religious aspirations.